A novel Hj-index based model to assess the researchers using scopus database - Lakshmi Devi, Voora V. V. Eswari; Amiripalli, Shanmuk Srinivas (Institute of Advanced Engineering and Science, 2024)
There are many factors that can influence the impact and influence of research, including the quality and originality of the research, relevance and importance of the research, clarity and effectiveness of the research communication, placement of the research in high-impact journals, collaboration and networking, and timing of the research. Identifying active genuine researcher is a sub problem of raising stars in a research area. This problem was addressed by enhancing H-index in Scopus database. Researchers should consider these factors when conducting and communicating their research to maximize its impact and influence. Additionally, there are several metrics used to evaluate the impact and influence of journals and researchers such as H-index, SNIP, CiteScore, and SJR. These metrics take into account different aspects of productivity and impact, and can provide a more comprehensive view of a journal or researcher's influence within their field. In addition to the above metrics, Hj-index was proposed and compared with the H-index to find active genuine researcher in a group.